Strategies for the development of logistics of cross-border electronic commerce: China’s experience - Meng, Zimin (Journal of the Belarusian State University. Economics, 2025)
This article examines China’s strategy for developing cross-border electronic commerce and related logistics based on an analysis of its phenomenal growth from 2020 to 2025. It identifies and describes the goals and tools for implementing this strategy, as well as the potential for applying its individual elements in the EAEU and Belarus. A consensus forecasting methodology for the development of international electronic commerce and related logistics is proposed. Based on this methodology, a forecast for the growth of cross-border electronic commerce volumes up to 2030 has been compiled, both globally and in China.
Keywords: cross-border electronic commerce; logistics of cross-border electronic commerce; Belt and Road Initiative